2012
DOI: 10.1001/jama.2012.3507
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for the Prevention and Treatment of Antibiotic-Associated Diarrhea

Abstract: Context Probiotics are live microorganisms intended to confer a health benefit when consumed. One condition for which probiotics have been advocated is the diarrhea that is a common adverse effect of antibiotic use. Objective To evaluate the evidence for probiotic use in the prevention and treatment of antibiotic-associated diarrhea (AAD). Data Sources Twelve electronic databases were searched (DARE, Cochrane Library of Systematic Reviews, CENTRAL, PubMed, EMBASE, CINAHL, AMED, MANTIS, TOXLINE, ToxFILE, NTIS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
146
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 691 publications
(157 citation statements)
references
References 71 publications
3
146
0
8
Order By: Relevance
“…The advice is graded as "A," "B," "C," or no category. Classified in the A-grade advice are probiotic Lactobacillus strains used to treat acute childhood diarrhea (101) and C. difficile-associated diarrhea (102). Probiotic Lactobacillus strains used to treat chronic disorders of the gut, including IBD, are classified as having B-grade advice because there have been some negative studies (103).…”
Section: Probiotic Lactobacillus Strains Isolated From the Human Intementioning
confidence: 99%
See 1 more Smart Citation
“…The advice is graded as "A," "B," "C," or no category. Classified in the A-grade advice are probiotic Lactobacillus strains used to treat acute childhood diarrhea (101) and C. difficile-associated diarrhea (102). Probiotic Lactobacillus strains used to treat chronic disorders of the gut, including IBD, are classified as having B-grade advice because there have been some negative studies (103).…”
Section: Probiotic Lactobacillus Strains Isolated From the Human Intementioning
confidence: 99%
“…Despite this lack of experimental evidence, the use of probiotic Lactobacillus strains to treat C. difficile-induced diarrhea has been extensively promoted in a high number of reviews (348-352), but it remains controversial (353). Meta-analyses have evidenced that probiotic strains are associated with a reduction in C. difficile-associated diarrhea (102,(354)(355)(356)(357). There were a small number of reports showing persuasive therapeutic effects against C. difficile-induced diarrhea after the administration of a single probiotic Lactobacillus strain.…”
Section: Therapeutic Effects Against C Difficile-associated Diarrheamentioning
confidence: 99%
“…A large number of LAB, isolated from various fermented foods in different parts of the world, had been studied for their probiotic potential and ability to produce important substances for foods and pharmaceutical preparation (BautistaGallego et al, 2013;Monteagudo-Mera et al, 2012;Tham, Peh, Bhat, & Liong, 2012). LAB have become the focus of probiotic research internationally and their health benefits in the prevention of diarrhoea (Hempel et al, 2012), reduction of the cholesterol level (Jones, Martoni, & Prakash, 2012), relief of both irritable bowel syndrome (Ducrotté, Sawant, & Jayanthi, 2012) and milk allergy in infants (Kekkonen et al, 2008) are well documented. However, these properties cannot be extrapolated or generalised for all probiotic strains as such effects are strain-specific and a considerable number of works are still required to affirm the benefits of each probiotic candidate (Aureli et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews and meta-analyses were completed for the use of probiotics in any AAD. In one analysis, the pooled results from 63 randomized control trials revealed a RR of 0.58 (95%CI: 0.50-0.68, P < 0.001) with an number needed to treat (NNT) of 13 [177] . Among those studies, a subset of 14 were randomized controlled trials for the prevention of CDI and pooled analysis revealed a RR of 0.29 (95%CI: 0.17-0.48, P < 0.001) with an NNT of 25.…”
Section: Probioticsmentioning
confidence: 99%